Biblical knowing : a scriptural epistemology of error - Johnson, Dru (James Clarke & Co, 2014)
The Christian Scriptures could be theologically described as beginning and ending with an epistemological outlook. The first episode of humanity's activity centers on the knowledge of good and evil. The final stage of humanity is pictured by Jeremiah as a universally prophetic and knowing society: ''And no longer shall each one teach his neighbor and each his brother, saying, ''Know the Lord'', for they shall all know me, from the least of them to the greatest, declares the Lord'' (Jer 31:34). What happens to knowledge in between? In this work, Dru Johnson reconsiders epistemology with the too.